Understanding the determinants of income inequality in Uganda - Ssewanyana, N; Okidi, A; Angemi, D; Barungi, V (2004)
This paper aims to deepen our understanding of the determinants of income inequality in Uganda. Over the past 10 years, Uganda experienced gradual and sustained economic growth and poverty reduction. The benefits of growth, however, are not being distributed equally. The major contributions of this paper include: (i) Use of income data to decompose the contribution of each income source to overall inequality; (ii) Decomposition of consumption expenditure into subgroups in order to examine the contribution of each subgroup to overall inequality using their between- and within-subgroup components, both spatially and over time; (iii) Regression-based inequality decomposition to identify and quantify the relative contribution of household and community level factors in determining inequality. The evidence supports the hypothesis that higher income groups, possessing more income generating assets (productive assets, human assets, or both), are in a better position to benefit from increased national income.